Hydrothermal Synthesis and Optical Properties of Undoped and \(Eu^3+\)-doped Zinc Stannate Nanocrystals - Thien, Nguyen Duy; Tu, Nguyen Ngoc; Viet, Ngo Nhu; Phuong, Nguyen Duy; Vu, Le Van; Long, Nguyen Ngoc (Communications in Physics, 2016)
Abstract. In this work we report a hydrothermal approach for synthesis of zinc stannate (Zn2SnO4)nanocrystals. Our research focused on the effect of the molar ratio of initial chemicals, reaction temperature and reaction duration on the phase composition and the fluorescence properties.Structural and optical properties of the final products were investigated in detail. X-ray diffractionanalysis indicated that the Zn2SnO4 nanocrystals possess face-centered cubic crystal structure.Raman scattering spectra exhibit two characteristic vibrational modes of Zn2SnO4 crystals. Optical band gap of Eu3+-doped Zn2SnO4 nanocrystals obviously depends on Eu3+content. Theroom-temperature emission spectra of the undoped Zn2SnO4 nanocrystals show two broad bands,while the photoluminescence spectra of Eu3+-doped Zn2SnO4 nanocrystals exhibit the emissionpeaks related to the radiative intra-configurational f-f tr ansitions of Eu3+ions. The absorptiontransitions within Eu3+ions were observed both in the photoluminescence excitation spectra andin the diffuse reflection spectra